Evaluasi Kinerja Perbankan Dengan Perspektif Balanced Scorecard: Studi Pada Perbankan Syariah Di Wilayah Purwokerto - - Mujayanah; Negina Kencono Putri; Uswatun Hasanah (Trunojoyo University of Madura, 2014)
This study aimed to test whether Islamic bank in Purwokerto is able to achieve good performance when measured by the Balanced Score Card (BSC) approach is based on the perspective of financial, customer, internal business processes and learning and growth.Research using the survey method with purposive sampling of employees and customers with a proportional random sampling method at Bank BNI Syariah and BRI Syariah Purwokerto. Hypothesis testing is performed using the Mann Whitney test as a tool for comparison of two independent samples test for ordinal data.The results showed BNI Syariah and BRI Syariah Purwokerto were able to achieve excellent performance when measured by the BSC approach based financial perspective and the perspective of growth and learning. Meanwhile, the performance of which is measured by the achievement of the BSC approach based on the customer perspective and internal business process perspective at Bank BNI Syariah and BRI Syariah Purwokerto were able to achieve a good performance level.The implication of this study is that the performance of Bank BNI Syariah and BRI Syariah Purwokerto is good when measured with the BSC approach should be maintained so as to provide satisfactory services for bank customers and employees can improve their performance so that organizational goals can be achieved. In addition, Bank BNI Syariah and BRI Syariah Purwokerto in order to make service excellence as a work culture within the company so that the company's performance can be maintained and enhanced.